Kinetics and Mechanism of the Adsorption of Methylene Blue from Aqueous Solution onto Turkish Green Clay - , Özkan Demirbaş; , Mehmet Salih Nas (Archives of Current Research International, 2016)
In this study, the thermodynamic parameters and adsorption kinetics of methylene blue (MB) onto Turkish green clay (TGC) from Gurpinar in Van, Turkey were investigated in aqueous solution through batch adsorption experiment. Turkish green clay was used in this study for the first time in the literature for this purpose. Adsorption studies were carried out to investigate the effect of experimental factors such as contact time (1-120 min), initial dye concentration (0.5-2.0x10-5 M), temperature (298-328 K) and pH (5.5-9) on the adsorption of MB. The Turkish green clay (TGC), methylene blue (MB) and MB adsorbed Turkish green clay (MB-TGC) were characterized by SEM, FTIR-ATR, TGA and BET surface area analysis. Three different kinetic models, pseudo-first-order, pseudo-second-order and intraparticle diffusion were used to fit the kinetics data. The pseudo-second-order model best described the experimental data. However, the adsorption of MB was more suitable to be controlled by an intra-particle diffusion mechanism. The thermodynamic activation parameters, such as enthalpy, entropy and Gibbs free energy were determined. The maximum adsorption capacity of TGC was found to be 195.74 mg/g (or 0.612 mmol/g) at pH 9, 298 K and 2.0x10-5 M, initial MB concentration of solution. These results showed that MB can be effectively removed from aqueous solution employing TGC as an adsorbent.